Soft skills among hearing impaired graduates for sustainability and well-being in workplace - Yong, Seh Sheh; Hanapi, Zaliza; Mustapha, Ramlee; Tee, Tze Kiong (Human Resource Management Academic Research Society, 2020)
Technical skill is not the only skill needed to secure an employment in the 21st century. Soft skills have become one of the basic needs nowadays and the most essential skill in industry for both common worker and hearing impaired worker. Graduates’ unemployment issue showed a gap exists between academic excellent and equipped soft skills. Therefore, this article was written to determine the elements needed to sustain soft skills among hearing impaired graduates in order to ensure sustainability and well-being in workplace. The research uses meta-analysis, interview and fuzzy Delphi method to get consensus from 11 experts consisting of four specialist educators, four employers and three graduates in relation to hearing impaired community. The findings show that, the expert consensus agreement exceeds 75% with threshold (d) value  0.2 and α-cut  0.5. The elements of the soft skills for hearing impaired graduates were sorted and ranked as personal qualities, basic skills, resource and information skills, interpersonal skills, thinking skills, entrepreneurship skills and system and technology skills. For future studies, it is recommended to develop an instrument based on the elements of this study to measure soft skills of hearing impaired graduates. Meanwhile, educational institutions must work hand in hand with industry to strengthen the soft skills among future hearing impaired worker through industry training programme to produce more competitive workforce, sustainability and well-being in the workplace.